Family environments, school resources, and educational outcomes - Kao, Grace; Park, Hyunjoon (Research in the sociology of education,, 2016)
Contributions come from authors spread around the globe, illuminating how the efficacy and ideologies of schooling variably unfold in differing national and historical contexts. Written by sociologists, anthropologists, economists, and cultural critics, this journal offers lively and accessible empirical work to a broad audience.